A Comparative Analysis of Defensive Routines and Theories-In-Use of Engineering and Non-Engineering Managers - Cudney, Elizabeth A. (International Journal of Management Excellence (ISSN: 2292-1648), 2014)
Engineering managers are managers who have an understanding of both the technical and business aspects of organizations. However, the success of an engineering manager depends on being knowledgeable in both the business and technical functions of an organization. There is a perception that engineers experience challenges in areas such as communication, conflict resolution, and leadership. Defensive routines are actions implemented as a result of being in an embarrassing or threatening situation. This research uses a case study approach to measure whether defensive routines are more common in engineering managers or non-engineering managers. 27 managers created case studies based on their unique experiences as managers. These case studies were scored and the results show that defensive routines are more common in engineering managers than non-engineering mangers.